Akibat Hukum yang Ditimbulkan Oleh Zihar Terhadap Perkawinan Ditinjau dari Undang-Undang dan Kompilasi Hukum Islam - Dintara Lubis, Syaddan (Prodi Tata Negara (Siyasah) IAIN Langsa, 2023)
a law will always be present as a guiding compass so that humans as social beings do not run away from the right path, but a law or regulation will create patterns and forms of life resulting from the impact of that law as well. This study shows directly from a legal perspective regarding the impact caused by Zihar on marriage in terms of the Law what's more, aggregation of Islamic Regulation. The examination strategi utilized in this study is the elucidating technique, this method will show patterns of problems in society as legal subjects, which are studied through the techniques that apply in the public eye and circumstances, perspectives, sees, on going cycle, the impact of a peculiarity. With this study, the results will be obtained from research on the legal consequences caused by zihar on a marital relationship.